Strategi Optimalisasi Penerimaan Pajak Daerah Di Kabupaten Demak - Nilaiana, Nilaiana; Kadi Sukarna; Muhammad Junaidi; Endah Pujiastuti; Aisyah Nurhaliza (Journal Juridisch, 2025)
This study aims to analyze strategies for optimizing local tax revenues in Demak Regency, which play a strategic role as the primary source of financing for development and public services. The urgency of this research lies in evaluating the regional tax policies that have not yet been fully optimized, resulting in limited funds to cover government expenditures. The novelty of this study lies in its comprehensive analysis of optimization strategies, including updating tax data, utilizing information technology, improving service quality, and enforcing strict legal measures. Furthermore, this research emphasizes the importance of inter-agency collaboration, particularly with the Regional Financial and Asset Management Agency, as well as education and socialization programs to enhance taxpayer awareness and compliance. Employing a normative juridical approach supported by primary data from interviews and secondary data from statutory regulations, the findings reveal that optimization of tax revenues can be achieved through integrated information systems, stronger supervision, and incentive schemes for compliant taxpayers. These findings are expected to contribute to strengthening local tax policy and supporting the sustainable improvement of public welfare in Demak Regency.   Penelitian ini bertujuan untuk menganalisis strategi optimalisasi penerimaan pajak daerah di Kabupaten Demak yang memiliki peran strategis sebagai sumber utama pembiayaan pembangunan dan pelayanan publik. Urgensi penelitian terletak pada evaluasi terhadap kebijakan penerimaan pajak daerah yang belum optimal, sehingga berdampak pada keterbatasan dana untuk menutupi kebutuhan belanja pemerintah daerah. Kebaruan penelitian ini terletak pada analisis komprehensif mengenai strategi optimalisasi yang mencakup pemutakhiran data perpajakan, pemanfaatan teknologi informasi, peningkatan kualitas pelayanan, serta penegakan hukum yang tegas. Selain itu, penelitian ini juga menekankan pentingnya kolaborasi lintas instansi, termasuk dengan Badan Pengelolaan Keuangan dan Pendapatan Aset Daerah, serta edukasi dan sosialisasi untuk meningkatkan kesadaran dan kepatuhan wajib pajak. Dengan menggunakan pendekatan yuridis normatif yang didukung oleh data primer melalui wawancara dan data sekunder berupa peraturan perundang-undangan, hasil penelitian menunjukkan bahwa optimalisasi penerimaan pajak dapat dicapai melalui integrasi sistem informasi, penguatan pengawasan, dan insentif bagi wajib pajak patuh. Temuan ini diharapkan memberikan kontribusi bagi penguatan kebijakan perpajakan daerah serta mendukung peningkatan kesejahteraan masyarakat Kabupaten Demak secara berkelanjutan.